Guidelines for Developing Voluntary Activities at Chulachomklao Royal Military Academy - Kaewsueb, Sathanee; Phongphotakul, Kanokrath (CRMA Journal of Humanities and Social Sciences, 2024)
This research aimed to: 1) Study the achievements of voluntary activities; 2) Investigate the problems and obstacles encountered during voluntary activities; and 3) Provide guidelines for developing the voluntary activities at Chulachomklao Royal Military Academy (CRMA). The research utilized mixed methodology. The research tools were questionnaires and interviews with key informants such as officers, CRMA cadets, and residents around the area of CRMA. The results indicated that the overall achievement score of the voluntary activities at CRMA was at a high level with higher scores in participation, satisfaction, and efficiency respectively. However, efficiency was found to be a major problem due to the lack of staff, tools, equipment, and facilities. In terms of satisfaction, key informants perceived that participation was compulsory rather than voluntary, burdening them with extra workloads. For participation, there was a lack of coordination with local community leaders. From these findings, the research recommended the following guidelines: 1) To improve efficiency, there should be an appropriate allocation of personnel, time, venues, budget, tools, equipment, and facilities; 2) To improve satisfaction, the target area of voluntary activities should be expanded and more forms of activities should be added; and 3) To improve participation, the principle of selfless service should be instilled more and voluntary activities should be publicized more extensively so that all stakeholders are able to participate in the activities.